2005
DOI: 10.1371/journal.pbio.0030093
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evolution of a cis-Regulatory Module

Abstract: Lack of knowledge about how regulatory regions evolve in relation to their structure–function may limit the utility of comparative sequence analysis in deciphering cis-regulatory sequences. To address this we applied reverse genetics to carry out a functional genetic complementation analysis of a eukaryotic cis-regulatory module—the even-skipped stripe 2 enhancer—from four Drosophila species. The evolution of this enhancer is non-clock-like, with important functional differences between closely related species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
203
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(212 citation statements)
references
References 37 publications
(37 reference statements)
8
203
0
Order By: Relevance
“…In addition, they uncovered several binding sites that have been gained and lost among these four species: a lineage-specific addition of the bicoid-3 binding site in D. melanogaster that is absent in the other species, a lineage-specific loss of the hunchback-1 site in D. yakuba, and the presence of an extra Kruppel site in D. pseudoobscura relative to D. melanogaster. These differences are nicely summarized in Figure 2B of Ludwig et al (2005).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, they uncovered several binding sites that have been gained and lost among these four species: a lineage-specific addition of the bicoid-3 binding site in D. melanogaster that is absent in the other species, a lineage-specific loss of the hunchback-1 site in D. yakuba, and the presence of an extra Kruppel site in D. pseudoobscura relative to D. melanogaster. These differences are nicely summarized in Figure 2B of Ludwig et al (2005).…”
mentioning
confidence: 76%
“…Ludwig et al (1998Ludwig et al ( , 2000Ludwig et al ( , 2005 studied the evolution of the even-skipped stripe 2 enhancer in four Drosophila species (Drosophila melanogaster, D. yakuba, D. erecta, and D. pseuodoobscura). While expression is strongly conserved, they found many substitutions in the binding sites for bicoid, hunchback, Kruppel, and giant, as well as large differences in the overall size of the enhancer region.…”
mentioning
confidence: 99%
“…3). We note that we are likely to be missing a number of targets of positive selection: gene expression varies across tissues and developmental stages 26 , and as a result, the absence of support for selection in primate expression data is weak evidence against it.…”
Section: Lettersmentioning
confidence: 89%
“…We found that comparative genomics resulted in many functionally meaningful sites for transcription factors Mef2, Twist and Snail outside ChIPbound regions, probably representing targets from diverse conditions not surveyed experimentally. Similarly, ChIP resulted in many additional sites outside those recovered by comparative genomics: some of these may have been replaced by functionally equivalent non-orthologous sequence, rendering them apparently non-conserved in sequence alignments [122][123][124] ; others may have species-or lineagespecific roles, thus lacking sufficient signal for their comparative detection; finally, some bound sites may be biochemically active yet selectively neutral 125 . It is worth noting, however, that ChIP-bound motifs that were not conserved showed decreased enrichment in muscle/ mesoderm development where the factors are known to act, suggesting that potential lineage-specific roles may lie outside the regulators' conserved functions.…”
Section: Discussionmentioning
confidence: 99%